The eucalypt woodlands of Western Australia: Lessons from the birds - Majer, Jonathan; Recher, H. F.; Davis Jr., W. E. (2010)
Despite the clearing of the wheatbelt, Western Australia retains the most extensive and least disturbed temperate woodlands in southern Australia. The Great Western Woodlands falls beyond the clearing line and is a 16 million hectare region of eucalypt woodland associated with mallee, heaths, and salt lakes (Watson et al. 2008). Although the Great Western Woodlands has a long history of disturbance by mining, roads, logging, and wildfires, a core of more than 6 million hectares has never been grazed by domestic stock, with large areas unaffected by mining or logging. The lack of grazing is particularly significant, as domestic grazers compact the soil, remove the litter layer and change the structure and species composition of the vegetation. Grazing may not be as severe an impact as clearing for farming (but see Majer et al. this book), a practice which continues in Western Australia (Fulton and Majer 2006), but ungrazed woodlands are a unique and precious heritage in the 21st century. Their management and conservation should be a national priority.